Fund Manager Characteristics and The Social Performance of Conventional Mutual Funds in Indonesia - Naufal, Muhammad Dzaki; Nainggolan, Yunieta Anny (Journal of Business and Management, 2015)
Abstract â€“ Socially responsible investment has been popular in the last decade due to the global concerns on ethical and environmental issues which cause high risk in the future. Socially responsible investment is also started to grow in Indonesia with the establishment of sustainability index, SRI-KEHATI, in 2009. Growing interests in SRI investment in Indonesia make us wonder whether conventional mutual funds also invest in companies with high social performance. Further, previous study in Indonesia mostly examines the financial performance of conventional funds or SRIs and there is no study yet which examines the social performance of conventional mutual funds and their determinants. Hence, this study aims to find the score the social performance of conventional equity mutual funds in Indonesia. We measure this using two ethical indices in Indonesia stock exchange, which are ISSI (Indonesia Sharia Stock Index) and SRI-KEHATI. This study period is only 2012 due to data availability. Further, we examine whether there is a relationship between fund manager characteristics such as gender and education background and this social performance. Our regression results show that there is no relationship between female fund managers and their asset allocation in firms with high social performance. However, we find that fund managers with master degree but not necessary from overseas university seem to invest in firms with high social performance which showing that higher degree may have provide them with higher concerns on environmental, social, and governance issues. We also find that older funds tend to hold shares that are socially responsible suggesting older funds may put higher concern on social than financial performance of their holdings due to lower market risk and the expectation of better performance in the future or in the long term.Â Keywords: Socially Responsible Investment Funds, Conventional Mutual Funds, Gender, Educational Background, Behavioral Finance, Fund Manager.